High-strength conductive anti-corrosion PVC pipe containing modified lithium slag and preparation method of high-strength conductive anti-corrosion PVC pipe

By introducing modified lithium slag and nanoconductive agents into PVC pipes, combined with basalt fibers and silicon carbide whiskers, the shortcomings in the existing PVC pipes in terms of mechanical, conductive and anti-corrosion properties are solved, and the comprehensive improvement of high strength, conductivity and corrosion resistance is achieved.

CN119875262AActive Publication Date: 2025-04-25JIANGXI BUILDING MATERIALS RES & DESIGN INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411988417.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing PVC pipes for coal mine construction have shortcomings in terms of mechanical properties, conductive properties and corrosion resistance, which are difficult to meet the high requirements of coal mine construction.

Method used

High-strength conductive PVC pipe containing modified lithium slag is used to chemically graft the ionic conductive polymer polyethylene oxide as the nanoparticle conductive agent by chemically grafting the surface of Ti3C2TX nanoparticles, and the modified lithium slag powder, basalt fibers and silicon carbide whisker composites are introduced as mechanical properties enhancement fillers.

Benefits of technology

It realizes the high strength, good conductivity and excellent corrosion resistance of PVC pipes, reduces production costs, and improves the safety and service life of the pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-strength conductive anticorrosive PVC pipe containing modified lithium slag and a preparation method thereof, and relates to the technical field of PVC pipes for buildings, the high-strength conductive PVC pipe containing modified lithium slag comprises the following components by weight: 100 parts of PVC resin, 8-12 parts of an impact modifier, 4-10 parts of a Ti3C2TX-polyethylene oxide nanoparticle conductive agent, 6-10 parts of modified lithium slag, and 1-3 parts of a lubricant, 3-6 parts of a heat stabilizer, 3-6 parts of a plasticizer, 1-2 parts of an anti-aging agent, 2-5 parts of a flame retardant and 0.1-0.3 part of a coloring agent. The high-strength conductive anti-corrosion PVC pipe is applied to coal mine pipeline construction, the mechanical strength is improved under the condition that the conductive performance requirement is met, and the acid and alkali corrosion resistance is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC pipes for construction, and in particular to a high-strength conductive anti-corrosion PVC pipe containing modified lithium slag and a preparation method thereof. Background Art

[0002] For a long time, my country's underground coal mine construction mainly uses glass fiber reinforced plastics and steel to manufacture drainage, ventilation, dust collection and gas extraction pipes. Glass fiber reinforced plastic pipes have high strength but are brittle when used, and are more easily damaged due to long-term aging and collision; steel pipes have high strength, but high density, weak corrosion resistance, complex installation, high maintenance and anti-corrosion costs and short service life. At present, the most widely used coal mine underground construction pipelines are basically made of PE and PVC, which have the advantages of light weight, corrosion resistance and toughness compared with glass fiber reinforced plastic pipes and steel pipes. Among them, PE pipes have high cost, low strength, poor flame retardancy, and inconvenient maintenance and installation. In particular, PE pipes are connected by hot melt welding and must use a heating power supply, which poses certain safety hazards. Compared with PE pipes, PVC pipes have their own advantages such as low manufacturing cost, good flame retardant effect and safe and reliable connection. In order to make PVC pipes better used in the field of coal mine pipeline construction, new requirements are put forward for PVC pipes, such as high mechanical properties, good electrical conductivity, and strong acid and alkali corrosion resistance. Summary of the invention

[0003] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art. In order to meet the above requirements for PVC pipes for coal mine construction, the present invention provides a high-strength conductive PVC pipe containing modified lithium slag and a preparation method thereof. 3 C 2 T X It is a new type of two-dimensional nanomaterial with high conductivity. 3 C 2 T X The surface of nanoparticles is chemically grafted with ionic conductive polymer polyethylene oxide as a nanoparticle conductive agent. On the one hand, the inorganic and organic conductive materials are chemically connected, and the close combination of the two enhances the conductive effect. On the other hand, PVC and polyethylene oxide are both polar polymers with good compatibility, which prevents Ti 3 C 2 T X Nanoparticles agglomerate, making them well dispersed in PVC resin, and the conductive properties are fully utilized. At the same time, the two-dimensional layered structure Ti 3 C 2 T XEvenly distributed in the PVC resin, it forms layers of dense flaky barrier layers, which play a good barrier role in preventing the invasion of corrosive media, thus giving the PVC pipe good corrosion resistance. The modified lithium slag powder / basalt fiber / silicon carbide whisker composite is used as a mechanical property enhancing filler, and the addition of coupling agent further enhances the tightness between lithium slag powder, basalt fiber, silicon carbide whisker and PVC resin and other additives. On the one hand, lithium slag powder replaces calcium carbonate powder, which greatly reduces the production cost of PVC pipe products while maintaining good hardness, stiffness and impact resistance; on the other hand, the addition of basalt fiber and silicon carbide whisker further enhances the mechanical strength and toughness of PVC pipes. By optimizing the formula of each component, a conductive and anti-corrosion PVC pipe with light weight, good toughness and high strength is prepared.

[0004] The technical solution of the present invention is as follows: The first aspect of the present invention provides a high-strength conductive anti-corrosion PVC pipe containing modified lithium slag, comprising the following raw materials in parts by weight: 100 parts of PVC resin, 8-12 parts of impact modifier, Ti 3 C 2 T X - 4 to 10 parts of polyethylene oxide nanoparticle conductive agent, 6 to 10 parts of modified lithium slag, 1 to 3 parts of lubricant, 3 to 6 parts of heat stabilizer, 3 to 6 parts of plasticizer, 1 to 2 parts of anti-aging agent, 2 to 5 parts of flame retardant, and 0.1 to 0.3 parts of colorant.

[0005] Optionally, the Ti 3 C 2 T X -The preparation method of polyethylene oxide nanoparticle conductive agent comprises: Add DMSO (dimethyl sulfoxide) solvent to the reaction vessel first, then add Ti 3 C 2 T X The powder is transferred to 60-80°C and stirred, and then the hydroxyl activator DBTO (di-n-butyltin oxide) is added, and the stirring is continued. The ethylene oxide monomer is added to the system and stirred for reaction. After the reaction is completed, centrifugal separation is performed, and the product is washed with anhydrous ethanol. Finally, the product is vacuum dried to obtain Ti 3 C 2 T X -Polyethylene oxide nanoparticles conductive agent.

[0006] Optionally, the DMSO solvent: Ti 3 C 2 T X The ratio of powder: DBTO: ethylene oxide monomer usage = 500~700mL: 8~12g: 0.05~0.15g: 2~2.4g.

[0007] Optionally, the method for preparing the modified lithium slag comprises: 1) Ball mill the lithium slag to obtain a specific surface area of ​​1000-1500 m 2 / kg of lithium slag fine powder; 2) uniformly mixing the chloroalkylsilane coupling agent and ethanol to prepare a chloroalkylsilane coupling agent / ethanol mixed solution; 3) adding basalt fiber into ethanol, ultrasonically dispersing, adding silicon carbide whiskers and ultrasonically dispersing, and drying to obtain a basalt fiber / silicon carbide whisker mixture; 4) The lithium slag fine powder and basalt fiber / silicon carbide whisker are stirred and the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed on the mixture. After the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed, the mixture is stirred evenly and then heated to 70-90° C. for 60-120 min to obtain modified lithium slag.

[0008] Optionally, in the preparation method of the modified lithium slag, the mass ratio of the chloroalkylsilane coupling agent to ethanol is 1-2:10-20, the mass ratio of the lithium slag to the chloroalkylsilane coupling agent is 20-40:1-2, and the mass ratio of the lithium slag, basalt fiber, and silicon carbide whisker is 5-10:1-5:1-5.

[0009] Optionally, in the method for preparing the modified lithium slag, the chloroalkylsilane coupling agent is at least one of 3-chloropropyltrimethoxysilane, 3-chloropropyltrichlorosilane and 3-chloropropyldimethoxysilane.

[0010] Optionally, the PVC resin is at least one of SG-4, SG-5, and SG-6 type polyvinyl chloride resins; The impact modifier is a mixture of CPE and MBS, and the weight ratio of CPE to MBS is 3 to 5:1; The lubricant is a mixture of stearic acid and PE wax, and the weight ratio of the stearic acid to the PE wax is 1 to 2:1; The heat stabilizer is at least one of a calcium zinc stabilizer and an organic tin stabilizer; The plasticizer is at least one of dioctyl phthalate and epoxy soybean oil; The flame retardant is at least one of aluminum hydroxide, magnesium hydroxide and antimony trioxide.

[0011] The second aspect of the present invention provides a method for preparing the above-mentioned high-strength conductive anti-corrosion PVC pipe containing modified lithium slag, comprising the following steps: S1. Put all the raw materials into a high-speed mixer according to the proportion and gradually heat them. Stir them thoroughly at 1000-1200r / min until the temperature of the mixture reaches 110-120°C. Then put the mixed materials into a cold mixing equipment and continue mixing at 400-500r / min until the temperature of the materials drops to 40-50°C. S2. Pour the mixed material into the hopper of a twin-screw extruder for melt extrusion, shaping, cooling and cutting to prepare the PVC pipe.

[0012] Optionally, in step S2, the temperatures of the twin-screw extruder barrel heating zones are: 160°C-165°C in zone 1, 165°C-170°C in zone 2, 170°C-175°C in zone 3, 175°C-180°C in zone 4, and 185°C-190°C in zone 5.

[0013] Optionally, in step S2, the temperatures of the heating zones of the molding die are: 185°C-190°C in zone one, 190°C-195°C in zone two, and 195°C-200°C in zone three.

[0014] The present invention has at least one of the following beneficial effects: The present invention first introduces a new type of highly conductive two-dimensional nanomaterial Ti 3 C 2 T X and through the Ti 3 C 2 T X The surface of nanoparticles is chemically grafted with ionic conductive polymer polyethylene oxide as a nanoparticle conductive agent. On the one hand, the inorganic and organic conductive materials are chemically connected, and the close combination of the two enhances the conductive effect. On the other hand, PVC and polyethylene oxide are both polar polymers with good compatibility, which prevents Ti 3 C 2 T X Nanoparticles agglomerate, making them well dispersed in PVC resin, and the conductive properties are fully utilized. At the same time, the two-dimensional layered structure Ti 3 C 2 T XIt is evenly distributed in the PVC resin to form layers of dense flaky barrier layers, which plays a good barrier role in preventing the invasion of corrosive media, thereby giving the pipe good corrosion resistance. Secondly, slag powder lithium slag is introduced, and the modified lithium slag powder / basalt fiber / silicon carbide whisker composite is used as a mechanical property enhancing filler, and the addition of coupling agent further enhances the tightness between lithium slag powder, basalt fiber, silicon carbide whisker and PVC resin and other additives. On the one hand, lithium slag powder replaces calcium carbonate powder, which greatly reduces the production cost of PVC pipe products while maintaining good hardness, stiffness and impact resistance; on the other hand, the addition of basalt fiber and silicon carbide whisker further enhances the mechanical strength and toughness of PVC pipes. Finally, by optimizing the formula of each component, a conductive and anti-corrosion PVC pipe with light weight, good toughness and high strength is prepared. DETAILED DESCRIPTION

[0015] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0016] One embodiment of the present invention provides a high-strength conductive anti-corrosion PVC pipe containing modified lithium slag, comprising the following raw materials in parts by weight: 100 parts of PVC resin, 8-12 parts of impact modifier, Ti 3 C 2 T X - 4-10 parts of polyethylene oxide nanoparticle conductive agent, 6-10 parts of modified lithium slag, 1-3 parts of lubricant, 3-6 parts of heat stabilizer, 3-6 parts of plasticizer, 1-2 parts of anti-aging agent, 2-5 parts of flame retardant, and 0.1-0.3 parts of colorant.

[0017] In some embodiments, the preparation raw materials include the following weight fractions: 100 parts of PVC resin, 9-11 parts of impact modifier, Ti 3 C 2 T X -6-8 parts of polyethylene oxide nanoparticle conductive agent, 7-9 parts of modified lithium slag, 1.5-2.5 parts of lubricant, 4-5 parts of heat stabilizer, 4-5 parts of plasticizer, 1.2-1.8 parts of anti-aging agent, 3-4 parts of flame retardant, and 0.15-0.25 parts of colorant.

[0018] In some embodiments, the preparation raw materials include the following weight fractions: 100 parts of PVC resin, 10 parts of impact modifier, Ti 3 C 2 T X- 7 parts of polyethylene oxide nanoparticle conductive agent, 8 parts of modified lithium slag, 2 parts of lubricant, 4.5 parts of heat stabilizer, 4.5 parts of plasticizer, 1.5 parts of anti-aging agent, 3.5 parts of flame retardant, and 0.2 parts of colorant.

[0019] In some embodiments, the PVC resin is at least one of SG-4, SG-5, and SG-6 polyvinyl chloride resins; preferably, the PVC resin is SG-5 polyvinyl chloride resin.

[0020] In some embodiments, the impact modifier is a mixture of CPE and MBS, and the weight ratio of the CPE to the MBS is 3 to 5:1; preferably, the weight ratio of the CPE to the MBS is 4:1.

[0021] In some embodiments, the lubricant is a mixture of stearic acid and PE wax, and the weight ratio of the stearic acid to the PE wax is 1 to 2:1; preferably, the weight ratio of the stearic acid to the PE wax is 2:1.

[0022] In some embodiments, the heat stabilizer is at least one of a calcium zinc stabilizer and an organotin stabilizer; preferably, the heat stabilizer is an organotin stabilizer.

[0023] In some embodiments, the plasticizer is at least one of diisooctyl phthalate (DOP) and epoxidized soybean oil (ESO); preferably, the plasticizer is diisooctyl phthalate (DOP).

[0024] In some embodiments, the flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, and antimony trioxide; preferably, the flame retardant is magnesium hydroxide.

[0025] In some embodiments, the Ti 3 C 2 T X -The preparation method of polyethylene oxide nanoparticle conductive agent comprises: Add DMSO solvent to the reaction vessel first, then add Ti 3 C 2 T X The powder was transferred to an oil bath at 60-80°C for mechanical stirring, and then the hydroxyl activator DBTO was added and stirred continuously. The ethylene oxide monomer was added to the system for stirring reaction. After the reaction was completed, the system was centrifuged and washed with anhydrous ethanol. Finally, the product was vacuum dried to obtain Ti 3 C 2 T X -Polyethylene oxide nanoparticle conductive agent. The reaction process is as follows: Preferably, the Ti 3 C2 T X -The preparation method of polyethylene oxide nanoparticle conductive agent comprises: First add DMSO (dimethyl sulfoxide) solvent into a three-necked round-bottom flask, then add Ti 3 C 2 T X The powder was transferred to a 70°C oil bath and mechanically stirred for 0.5 h, and then a hydroxyl activator DBTO (di-n-butyltin oxide) was added. After stirring for 0.5 h, ethylene oxide monomer was added to the system and stirred for 12 h. After the reaction was completed, centrifugation was performed and the product was washed with anhydrous ethanol 5 times. Finally, the product was placed in a vacuum oven at 60°C and vacuum dried for 24 h to obtain Ti 3 C 2 T X -Polyethylene oxide nanoparticles conductive agent; DMSO:Ti 3 C 2 T X The ratio of powder: DBTO: ethylene oxide monomer usage = 600mL: 10g: 0.1g: 2.2g.

[0026] In some embodiments, the DMSO solvent: Ti 3 C 2 T X The ratio of powder: DBTO: ethylene oxide monomer is 500~700mL: 8~12g: 0.05~0.15g: 2~2.4g. Preferably, DMSO: Ti 3 C 2 T X The ratio of powder: DBTO: ethylene oxide monomer usage = 600mL: 10g: 0.1g: 2.2g.

[0027] In some embodiments, the method for preparing the modified lithium slag comprises: 1) The lithium slag is ball-milled to obtain a specific surface area of ​​1200 m 2 / kg of lithium slag fine powder; 2) uniformly mixing the chloroalkylsilane coupling agent and ethanol to prepare a chloroalkylsilane coupling agent / ethanol mixed solution; 3) adding basalt fiber into ethanol, ultrasonically dispersing, adding silicon carbide whiskers and ultrasonically dispersing, and drying to obtain a basalt fiber / silicon carbide whisker mixture; 4) The lithium slag fine powder and basalt fiber / silicon carbide whisker are stirred, and the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed on the surface of the lithium slag powder / basalt fiber / silicon carbide whisker composite. After the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed, the mixture is stirred evenly, and then heated to 80° C. for 90 minutes to obtain a modified lithium slag, that is, a modified lithium slag powder / basalt fiber / silicon carbide whisker composite.

[0028] Preferably, in the preparation method of the modified lithium slag powder / basalt fiber / silicon carbide whisker composite, the mass ratio of the chloroalkyl silane coupling agent to ethanol is 1:10, the mass ratio of the lithium slag to the chloroalkyl silane coupling agent is 20:1, and the mass ratio of the lithium slag, basalt fiber and silicon carbide whisker is 4:1:1.

[0029] Preferably, the high-strength conductive and corrosion-resistant PVC pipe containing modified lithium slag is characterized in that the chloroalkylsilane coupling agent is 3-chloropropyltrimethoxysilane.

[0030] Another embodiment of the present invention provides a method for preparing a high-strength conductive and corrosion-resistant PVC pipe containing modified lithium slag, comprising the following steps: S1. Put each component in a high-speed mixer according to the proportion and gradually heat it. Stir it thoroughly at 1000r / min until the temperature of the mixture reaches 110°C. Then put the mixed material into a cold mixing equipment and continue mixing at 500r / min until the temperature of the material drops to 50°C. S2. Pour the mixed material into the hopper of a twin-screw extruder for melt extrusion, shaping, cooling and cutting to prepare the PVC pipe.

[0031] Preferably, the method for preparing a high-strength conductive and corrosion-resistant PVC pipe containing modified lithium slag is characterized in that, in the step S2, the temperature of the heating zone of the twin-screw extruder barrel is: 165°C in zone 1, 170°C in zone 2, 175°C in zone 3, 180°C in zone 4, and 185°C in zone 5; the temperature of the heating zone of the molding mold is: 190°C in zone 1, 195°C in zone 2, and 200°C in zone 3.

[0032] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0033] The PVC resin used in the following examples and comparative examples is specifically SG-5 type polyvinyl chloride resin, the model of the anti-aging agent is antioxidant 1010, the flame retardant is specifically modified industrial grade magnesium hydroxide flame retardant (mesh size is 1250-3000), the heat stabilizer is specifically calcium zinc stabilizer CZX-768, the plasticizer is specifically DOP (117-84-0), the heat stabilizer is specifically organic tin stabilizer TM181, the colorant is specifically pigment red 53:1 (5160-02-1), and the chloroalkyl silane coupling agent is specifically 3-chloropropyltrimethoxysilane.

[0034] Example 1 1. Ti 3 C 2 T X -Preparation of Polyethylene Oxide Nanoparticle Conductive Agent: First, add 600 mL of DMSO (dimethyl sulfoxide) solvent into a three-necked round-bottom flask, then add 10 g of Ti 3 C 2 T X The powder was transferred to a 70°C oil bath and mechanically stirred for 0.5h, then 0.1g DBTO (di-n-butyltin oxide) as a hydroxyl activator was added, and stirring was continued for 0.5h. Then 2.2g ethylene oxide monomer was added to the system and stirred for 12h. After the reaction was completed, centrifugation was performed and the product was washed with anhydrous ethanol 5 times. Finally, the product was placed in a vacuum oven at 60°C and vacuum dried for 24h to obtain Ti 3 C 2 T X -Polyethylene oxide nanoparticles conductive agent.

[0035] 2. Preparation of modified lithium slag: 1) Take a certain amount of lithium slag and ball mill it to obtain a specific surface area of ​​1200 m 2 / kg of lithium slag fine powder; 2) Mix 1 g of chloroalkylsilane coupling agent and 10 g of ethanol to prepare a chloroalkylsilane coupling agent / ethanol mixed solution; 3) Add 5 g of basalt fiber to 50 mL of ethanol and disperse by ultrasonic. Then add 5 g of silicon carbide whisker and disperse by ultrasonic. Then, dry the mixture to obtain 10 g of basalt fiber / silicon carbide whisker. 4) The 20 g lithium slag fine powder and 10 g basalt fiber / silicon carbide whisker are stirred, and the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed on the surface of the 30 g lithium slag powder / basalt fiber / silicon carbide whisker composite. After the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed, the mixture is stirred evenly, and then heated to 80° C. for 90 min to obtain 30 g modified lithium slag, i.e., a modified lithium slag powder / basalt fiber / silicon carbide whisker composite.

[0036] 3. Preparation of high-strength conductive PVC pipe containing modified lithium slag: S1. Put each component in a high-speed mixer according to the proportion and gradually heat it. Stir it thoroughly at 1000r / min until the temperature of the mixture reaches 110°C. Then put the mixed material into a cold mixing equipment and continue mixing at 500r / min until the temperature of the material drops to 50°C. S2. Pour the mixed material into the hopper of a twin-screw extruder for melt extrusion, shaping, cooling and cutting to prepare the PVC pipe.

[0037] Among them, the temperatures of the twin-screw extruder barrel heating zones in step S2 are: 165°C in zone 1, 170°C in zone 2, 175°C in zone 3, 180°C in zone 4, and 185°C in zone 5; the temperatures of the molding die heating zones are: 190°C in zone 1, 195°C in zone 2, and 200°C in zone 3.

[0038] 4. Formula ratio of each component of high-strength conductive anti-corrosion PVC pipe containing modified lithium slag: PVC resin 100 parts, impact modifier 10 parts (CPE 8 parts, MBS 2 parts), Ti 3 C 2 T X -6 parts of polyethylene oxide nanoparticle conductive agent, 6 parts of modified lithium slag, 1.5 parts of lubricant (1 part of stearic acid, 0.5 parts of PE wax), 4 parts of heat stabilizer, 5 parts of plasticizer, 1.5 parts of anti-aging agent, 3 parts of flame retardant, and 0.2 parts of colorant.

[0039] Example 2 1. Ti 3 C 2 T X -Preparation of Polyethylene Oxide Nanoparticle Conductive Agent: First, add 600 mL of DMSO (dimethyl sulfoxide) solvent into a three-necked round-bottom flask, then add 10 g of Ti 3 C 2 T X The powder was transferred to a 70°C oil bath and mechanically stirred for 0.5h, then 0.1g DBTO (di-n-butyltin oxide) as a hydroxyl activator was added, and stirring was continued for 0.5h. Then 2.2g ethylene oxide monomer was added to the system and stirred for 12h. After the reaction was completed, centrifugation was performed and the product was washed with anhydrous ethanol 5 times. Finally, the product was placed in a vacuum oven at 60°C and vacuum dried for 24h to obtain Ti 3 C 2 T X -Polyethylene oxide nanoparticles conductive agent.

[0040] 2. Preparation of modified lithium slag: 1) Take a certain amount of lithium slag and ball mill it to obtain a specific surface area of ​​1200 m 2 / kg of lithium slag fine powder; 2) Mix 1 g of chloroalkylsilane coupling agent and 10 g of ethanol to prepare a chloroalkylsilane coupling agent / ethanol mixed solution; 3) Add 5 g of basalt fiber to 50 mL of ethanol and disperse by ultrasonic. Then add 5 g of silicon carbide whisker and disperse by ultrasonic. Then, dry the mixture to obtain 10 g of basalt fiber / silicon carbide whisker. 4) The 20 g lithium slag fine powder and 10 g basalt fiber / silicon carbide whisker are stirred, and the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed on the surface of the 30 g lithium slag powder / basalt fiber / silicon carbide whisker composite. After the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed, the mixture is stirred evenly, and then heated to 80° C. for 90 min to obtain 30 g modified lithium slag, i.e., a modified lithium slag powder / basalt fiber / silicon carbide whisker composite.

[0041] 3. Preparation of high-strength conductive PVC pipe containing modified lithium slag: S1. Put each component in a high-speed mixer according to the proportion and gradually heat it. Stir it thoroughly at 1000r / min until the temperature of the mixture reaches 110°C. Then put the mixed material into a cold mixing equipment and continue mixing at 500r / min until the temperature of the material drops to 50°C. S2. Pour the mixed material into the hopper of a twin-screw extruder for melt extrusion, shaping, cooling and cutting to prepare the PVC pipe.

[0042] Among them, the temperatures of the twin-screw extruder barrel heating zones in step S2 are: 165°C in zone 1, 170°C in zone 2, 175°C in zone 3, 180°C in zone 4, and 185°C in zone 5; the temperatures of the molding die heating zones are: 190°C in zone 1, 195°C in zone 2, and 200°C in zone 3.

[0043] 4. Formula ratio of each component of high-strength conductive anti-corrosion PVC pipe containing modified lithium slag: PVC resin 100 parts, impact modifier 10 parts (CPE 8 parts, MBS 2 parts), Ti 3 C 2 T X - 8 parts of polyethylene oxide nanoparticle conductive agent, 6 parts of modified lithium slag, 1.5 parts of lubricant (1 part of stearic acid, 0.5 parts of PE wax), 4 parts of heat stabilizer, 5 parts of plasticizer, 1.5 parts of anti-aging agent, 3 parts of flame retardant, and 0.2 parts of colorant.

[0044] Example 3 1. Ti 3 C2 T X -Preparation of Polyethylene Oxide Nanoparticle Conductive Agent: First, add 600 mL of DMSO (dimethyl sulfoxide) solvent into a three-necked round-bottom flask, then add 10 g of Ti 3 C 2 T X The powder was transferred to a 70°C oil bath and mechanically stirred for 0.5h, then 0.1g DBTO (di-n-butyltin oxide) as a hydroxyl activator was added, and stirring was continued for 0.5h. Then 2.2g ethylene oxide monomer was added to the system and stirred for 12h. After the reaction was completed, centrifugation was performed and the product was washed with anhydrous ethanol 5 times. Finally, the product was placed in a vacuum oven at 60°C and vacuum dried for 24h to obtain Ti 3 C 2 T X -Polyethylene oxide nanoparticles conductive agent.

[0045] 2. Preparation of modified lithium slag: 1) Take a certain amount of lithium slag and ball mill it to obtain a specific surface area of ​​1200 m 2 / kg of lithium slag fine powder; 2) Mix 1 g of chloroalkylsilane coupling agent and 10 g of ethanol to prepare a chloroalkylsilane coupling agent / ethanol mixed solution; 3) Add 5 g of basalt fiber to 50 mL of ethanol and disperse by ultrasonic. Then add 5 g of silicon carbide whisker and disperse by ultrasonic. Then, dry the mixture to obtain 10 g of basalt fiber / silicon carbide whisker. 4) The 20 g lithium slag fine powder and 10 g basalt fiber / silicon carbide whisker are stirred, and the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed on the surface of the 30 g lithium slag powder / basalt fiber / silicon carbide whisker composite. After the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed, the mixture is stirred evenly, and then heated to 80° C. for 90 min to obtain 30 g modified lithium slag, i.e., a modified lithium slag powder / basalt fiber / silicon carbide whisker composite.

[0046] 3. Preparation of high-strength conductive PVC pipe containing modified lithium slag: S1. Put each component in a high-speed mixer according to the proportion and gradually heat it. Stir it thoroughly at 1000r / min until the temperature of the mixture reaches 110°C. Then put the mixed material into a cold mixing equipment and continue mixing at 500r / min until the temperature of the material drops to 50°C. S2. Pour the mixed material into the hopper of a twin-screw extruder for melt extrusion, shaping, cooling and cutting to prepare the PVC pipe.

[0047] Among them, the temperatures of the twin-screw extruder barrel heating zones in step S2 are: 165°C in zone 1, 170°C in zone 2, 175°C in zone 3, 180°C in zone 4, and 185°C in zone 5; the temperatures of the molding die heating zones are: 190°C in zone 1, 195°C in zone 2, and 200°C in zone 3.

[0048] 4. Formula ratio of each component of high-strength conductive anti-corrosion PVC pipe containing modified lithium slag: PVC resin 100 parts, impact modifier 10 parts (CPE 8 parts, MBS 2 parts), Ti 3 C 2 T X - 10 parts of polyethylene oxide nanoparticle conductive agent, 6 parts of modified lithium slag, 1.5 parts of lubricant (1 part of stearic acid, 0.5 parts of PE wax), 4 parts of heat stabilizer, 5 parts of plasticizer, 1.5 parts of anti-aging agent, 3 parts of flame retardant, and 0.2 parts of colorant.

[0049] Comparative Example 1 The only difference from Example 1 is that no Ti is added 3 C 2 T X - Polyethylene oxide nanoparticle conductive agent and modified lithium slag, but 14 parts of calcium carbonate are added instead. Others are the same as in Example 1.

[0050] Comparative Example 2 The only difference from Example 1 is that 6 parts of calcium carbonate are added instead of modified lithium slag. The rest is the same as Example 1.

[0051] Comparative Example 3 The only difference from Example 1 is that no Ti is added 3 C 2 T X -Polyethylene oxide nanoparticle conductive agent, but 8 parts of calcium carbonate are added instead. Other parts are the same as in Example 1.

[0052] Comparative Example 4 The only difference from Example 1 is that no Ti is added 3 C 2 T X -Polyethylene oxide nanoparticle conductive agent, but instead add 6 parts of unmodified Ti 3 C 2 T X The rest is the same as in Example 1.

[0053] Comparative Example 5 The only difference from Example 1 is that: instead of adding modified lithium slag, 6 parts of unmodified lithium slag are added, and the lithium slag is only ground in step 1) of "preparation of modified lithium slag" in Example 1, and other steps are not performed. The rest is the same as Example 1.

[0054] Comparative Example 6 The raw materials and proportions are the same as those in Example 1, and the only difference from Example 1 is that the temperature of the heating zone of the twin-screw extruder barrel in step S2 of the preparation method is: 165°C in zone 1, 165°C in zone 2, 165°C in zone 3, 165°C in zone 4, and 165°C in zone 5; the temperature of the heating zone of the molding die is: 190°C in zone 1, 190°C in zone 2, and 190°C in zone 3. Others are the same as in Example 1.

[0055] Table 1 Specific addition amount of each raw material in Examples 1 to 3 and Comparative Examples 1 to 6 The PVC pipes prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to performance tests, and the test results are shown in Figure 2. Among them, the conductivity test selected the standard GB / T15662-1995; the acid and alkali corrosion resistance test selected the standard GB / T11547-2008: sulfuric acid (75%), sodium hydroxide (40%), sodium chloride (10%) as the test medium, the test immersion time (7 weeks), and the immersion temperature 60°C; the tensile performance test selected the standard GB / T1040-1992: the tensile rate was 50 mm / min, and the original gauge length was 100 mm; the bending performance test selected the standard GB / T9341-2000: the span was 60 mm, and the rate was 2 mm / min; the impact performance test selected the standard GB / T1043-1993: the distance between the support lines was 60 mm. Table 2 Performance test of high-strength conductive anti-corrosion PVC pipes containing modified lithium slag in Examples 1-3 and Comparative Examples 1-6 It can be seen from Table 2 that the high-strength conductive anti-corrosion PVC pipe containing modified lithium slag prepared in Examples 1 to 3 has a low resistance value, indicating that the PVC pipe has a certain conductivity; the tensile strength, impact strength, and bending strength are good, indicating that the mechanical properties of the PVC pipe are good; and the acid, alkali and salt resistance are good, indicating that the PVC pipe has good corrosion resistance.

[0056] Comparing Examples 1 to 3 with Comparative Examples 1 to 6, it can be seen that, firstly, Comparative Example 1 (without Ti 3 C 2 T X -polyethylene oxide nanoparticle conductive agent and modified lithium slag) is greater than that of Example 1, and the tensile strength, impact strength, bending strength, acid resistance, alkali resistance and salt resistance are significantly lower than those of Example 1, indicating that whether Ti is added 3 C 2 T X-Polyethylene oxide nanoparticle conductive agent and modified lithium slag will affect the conductivity, mechanical properties and corrosion resistance of PVC pipes; similarly, comparative example 3 (without Ti 3 C 2 T X -polyethylene oxide nanoparticle conductive agent) has a greater resistance value than Example 1, and its tensile strength, impact strength, bending strength, acid resistance, alkali resistance and salt resistance are significantly lower than those of Example 1, indicating that whether Ti is added 3 C 2 T X -Polyethylene oxide nanoparticle conductive agent will affect the conductivity, mechanical properties and corrosion resistance of PVC pipes; and the tensile strength, impact strength and bending strength of comparative example 3 are higher than those of comparative example 1, indicating that whether or not to add modified lithium slag has a greater impact on the mechanical properties of PVC pipes; in this regard, comparative example 2 also supports this conclusion. The tensile strength, impact strength and bending strength of comparative example 2 (without modified lithium slag) are significantly lower than those of example 1, but the resistance value, acid resistance, alkali resistance and salt resistance are comparable to those of example 1. Secondly, comparative example 4 (using unmodified Ti 3 C 2 T X The resistance value of the powder is slightly higher than that of Example 1, and the tensile strength, impact strength and bending strength are slightly lower than those of Example 1, indicating whether the Ti 3 C 2 T X Modification of the powder will affect the conductivity and mechanical strength of the PVC pipe; the resistance value, acid resistance, alkali resistance and salt resistance of Comparative Example 5 (using unmodified lithium slag) are comparable to those of Example 1, and the tensile strength, impact strength and bending strength are significantly lower than those of Example 1, indicating that whether the lithium slag is modified will affect the mechanical strength of the PVC pipe. Finally, the resistance value, acid resistance, alkali resistance and salt resistance of Comparative Example 6 (the temperature of each heating zone of the twin-screw extruder barrel is the same, and the temperature of each heating zone of the molding die is the same) are comparable to those of Example 1, and the tensile strength, impact strength and bending strength are lower than those of Example 1, indicating that the temperature of the heating zone will also affect the mechanical strength of the PVC pipe.

[0057] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-strength conductive anti-corrosion PVC pipe containing modified lithium slag, characterized in that: The preparation comprises the following raw materials in parts by weight: 100 parts of PVC resin, 8-12 parts of impact modifier, Ti3C2T X - 4 to 10 parts of polyethylene oxide nanoparticle conductive agent, 6 to 10 parts of modified lithium slag, 1 to 3 parts of lubricant, 3 to 6 parts of heat stabilizer, 3 to 6 parts of plasticizer, 1 to 2 parts of anti-aging agent, 2 to 5 parts of flame retardant, and 0.1 to 0.3 parts of colorant.

2. The high-strength conductive anti-corrosion PVC pipe containing modified lithium slag according to claim 1, characterized in that: The Ti3C2T X -The preparation method of polyethylene oxide nanoparticle conductive agent comprises: DMSO solvent was first added to the reaction vessel, and then Ti3C2T X The powder was transferred to 60-80°C and stirred, and then the hydroxyl activator DBTO was added and stirred. The ethylene oxide monomer was added to the system and stirred for reaction. After the reaction was completed, it was centrifuged and washed with anhydrous ethanol. Finally, the product was vacuum dried to obtain Ti3C2T X -Polyethylene oxide nanoparticles conductive agent.

3. The high-strength conductive anti-corrosion PVC pipe containing modified lithium slag according to claim 2, characterized in that: The DMSO solvent: Ti3C2T X The ratio of powder: DBTO: ethylene oxide monomer usage = 500~700mL: 8~12g: 0.05~0.15g: 2~2.4g.

4. The high-strength conductive anti-corrosion PVC pipe containing modified lithium slag according to claim 1, characterized in that: The preparation method of the modified lithium slag comprises: 1) Ball mill the lithium slag to obtain a specific surface area of ​​1000-1500 m 2 / kg of lithium slag fine powder; 2) uniformly mixing the chloroalkylsilane coupling agent and ethanol to prepare a chloroalkylsilane coupling agent / ethanol mixed solution; 3) adding basalt fiber into ethanol, ultrasonically dispersing, adding silicon carbide whiskers and ultrasonically dispersing, and drying to obtain a basalt fiber / silicon carbide whisker mixture; 4) The lithium slag fine powder and basalt fiber / silicon carbide whisker are stirred and the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed on the mixture. After the chloroalkyl silane coupling agent / ethanol mixed solution is sprayed, the mixture is stirred evenly and then heated to 70-90° C. for 60-120 min to obtain modified lithium slag.

5. The high-strength conductive anti-corrosion PVC pipe containing modified lithium slag according to claim 4, characterized in that: In the preparation method of the modified lithium slag, the mass ratio of the chloroalkylsilane coupling agent to ethanol is 1-2:10-20, the mass ratio of the lithium slag to the chloroalkylsilane coupling agent is 20-40:1-2, and the mass ratio of the lithium slag, basalt fiber and silicon carbide whisker is 5-10:1-5:1-5.

6. The high-strength conductive anti-corrosion PVC pipe containing modified lithium slag according to claim 4, characterized in that: In the method for preparing the modified lithium slag, the chloroalkylsilane coupling agent is at least one of 3-chloropropyltrimethoxysilane, 3-chloropropyltrichlorosilane and 3-chloropropyldimethoxysilane.

7. The high-strength conductive and anti-corrosion PVC pipe containing modified lithium slag according to claim 1, characterized in that: The PVC resin is at least one of SG-4, SG-5 and SG-6 type polyvinyl chloride resins; The impact modifier is a mixture of CPE and MBS, and the weight ratio of CPE to MBS is 3 to 5:1; The lubricant is a mixture of stearic acid and PE wax, and the weight ratio of the stearic acid to the PE wax is 1 to 2:1; The heat stabilizer is at least one of a calcium zinc stabilizer and an organic tin stabilizer; The plasticizer is at least one of dioctyl phthalate and epoxy soybean oil; The flame retardant is at least one of aluminum hydroxide, magnesium hydroxide and antimony trioxide.

8. The method for preparing a high-strength conductive and corrosion-resistant PVC pipe containing modified lithium slag according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Put all the raw materials into a high-speed mixer according to the proportion and gradually heat them. Stir them thoroughly at 1000-1200r / min until the temperature of the mixture reaches 110-120°C. Then put the mixed materials into a cold mixing equipment and continue mixing at 400-500r / min until the temperature of the materials drops to 40-50°C. S2, pouring the mixed material into the hopper of a twin-screw extruder for melt extrusion, shaping, cooling and cutting to prepare the PVC pipe.

9. The method for preparing a high-strength conductive and anti-corrosion PVC pipe containing modified lithium slag according to claim 8, characterized in that: In step S2, the temperatures of the heating zones of the twin-screw extruder barrel are: 160°C-165°C in zone 1, 165°C-170°C in zone 2, 170°C-175°C in zone 3, 175°C-180°C in zone 4, and 185°C-190°C in zone 5.

10. The method for preparing a high-strength conductive and anti-corrosion PVC pipe containing modified lithium slag according to claim 8, characterized in that: In step S2, the temperatures of the heating zones of the molding die are: 185°C-190°C in zone 1, 190°C-195°C in zone 2, and 195°C-200°C in zone 3.

Citation Information

Patent Citations

  • Conductive polyester composite material as well as preparation method and application thereof

    CN111978701A

  • Alkali-corrosion-resistant high-strength flexible polyvinyl chloride membrane material and preparation method thereof

    CN113214571A

  • MXene-graphene-PVC composite material and preparation method thereof

    CN114031867A

  • Solid waste-based PVC calendering film matrix wear-resistant material and preparation method thereof

    CN117004147A

  • Tool test device

    KR1020240142780A